Study of the essential oils of Thymus haussknechtii Velen and Thymus kotschyanus Boiss. et Hohen var. kotschyanus (Lamiaceae) taxa from the eastern Anatolian region in Turkey - Bagci, E; Baser, KHC (John Wiley & Sons Ltd, 2005)
The essential oils of water distilled aerial parts of Thymus haussknechtii and Thymus kotschyanus var. kotschyanus (Lamiaceae) were analysed by GC/MS system. Seventy-eight components were identified comprising 88.0 and 91.3% of the total components in the oils, respectively. 1,8-Cineole (21.5%) was the dominant compound in Thymus haussknechtii oil and thymol (47.5%) was the main component in the oil of Thymus kotschyanus var. kotschyanus. Copyright (c) 2004 John Wiley & Sons, Ltd.
Keywords: Thymus haussknechtii; Thymus kotschyanus; Lamiaceae; essential oil; 1,8-cineole; thymol; carvacrol